2022
DOI: 10.1002/jeab.755
|View full text |Cite
|
Sign up to set email alerts
|

The influence of reinforcement schedule on experience‐dependent changes in motivation

Abstract: The progressive ratio procedure is used across fields to assess motivation for different reinforcers, define the effects of experimental interventions on motivation, and determine experience‐dependent changes in motivation. However, less is known about how operant training schedules affect performance on this widely utilized task. Here we designed an experiment to examine the effect of variable ratio versus fixed ratio training schedules of reinforcement on progressive ratio performance while holding other per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…PR tasks are used to analyze motivation for various reinforcers, that is, the willingness of the organism to exert effort in order to obtain a reward. 29 In our work, the number of responses required to earn a food pellet in the PR experiments escalated as follows: 1‐2‐3‐5‐12‐18‐27‐40‐60‐90‐135‐200‐300‐450‐675‐1000. The PR session was performed only once and lasted for 2 h or until rats failed to complete the response requirement for delivery of a reinforcer within 1 h. The breakpoint for the extinction of food‐maintained operant behavior was determined for each animal.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…PR tasks are used to analyze motivation for various reinforcers, that is, the willingness of the organism to exert effort in order to obtain a reward. 29 In our work, the number of responses required to earn a food pellet in the PR experiments escalated as follows: 1‐2‐3‐5‐12‐18‐27‐40‐60‐90‐135‐200‐300‐450‐675‐1000. The PR session was performed only once and lasted for 2 h or until rats failed to complete the response requirement for delivery of a reinforcer within 1 h. The breakpoint for the extinction of food‐maintained operant behavior was determined for each animal.…”
Section: Methodsmentioning
confidence: 94%
“…PR tasks are used to analyze motivation for various reinforcers, that is, the willingness of the organism to exert effort in order to obtain a reward 29 . In our work, the number of responses required to earn a food pellet in the PR experiments escalated as follows: 1‐2‐3‐5‐12‐18‐27‐40‐60‐90‐135‐200‐300‐450‐675‐1000.…”
Section: Methodsmentioning
confidence: 99%
“…Both the preferential reinforcement of long inter-response times (IRT) in RI schedules (Krame & Rilling, 1970; Kuch & Platt, 1976) and the stronger action-outcome correlation in RR schedules (Dickinson, 1985; Ferster & Skinner, 1957; Pérez et al, 2019 although see Garr et al, 2020) are thought to contribute to generating this difference, and our finding that response rates are more sensitive to food restriction level in mice trained on RR schedules compared to RI schedules complements these interpretations. Furthermore, previous work has shown that while training schedule has little effects on motivation (Johnson et al, 2022), food restriction levels do impact it (Dietze et al, 2016; Malikovic et al, 2018). By manipulating food restriction levels, our findings provide further support to the notion that the ability to control one’s own reinforcement rate explains the difference in response rates generated by RR and RI schedules.…”
Section: Discussionmentioning
confidence: 99%
“…After reaching criteria at FR3, mice were tested in a 1-day progressive ratio task. The progressive ratio task was based on a protocol modified for mice by Johnson et al (2022 35 ), but with a maximum session time of 30 min. Mice were excluded if they failed to reach criteria after 10 days.…”
Section: Methodsmentioning
confidence: 99%